PERFORMANCE OPTIMIZATION OF BEAM CONCRETE BEAMS TO INCREASE BUILDING STRUCTURE PERFORMANCE IN EARTHQUAKE AREA - Agus Santoso; Slamet Widodo; Nuryadin Eko Raharjo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The paper summarizes the experimental result of flexural capacity of full scale reinforced concrete beam prepared as a composite members consisting of two concrete layers made of Hybrid Fiber Reinforced Concrete (HFRC) and High Strength Concrete (HSC). Compressive strength and modulus of elasticity test, splitting tensile, flexural tensile tests conducted to identify the important mechanical properties of both HFRC and HSC. Every mechanical properties data collected using 3 standard samples based on ASTM and SNI codes. 15 reinforced concrete beams in 150x250x2400 mm dimensions, usedfor full scale flexural test of structural RC beam. The tests conducted on 5 types of composite beam: 100%, 75%, 50%, 25%, and 0% of HSC cross sectional depth, combined with HFRC for the opposite sides.The experimental results indicated that HFRC shows higher modulus elasticity compared with HSC, it was 28618,611MPafor HFRC, and 21790,660 MPafor HSC. All types of composite members and full depth of HFRC shows higher first crack load capacity compared with HSC structural reinforced concrete beam. The first crack load capacity increase ranging from 29,753% up to 33,267%. All types of composite members and full depth of HFRC also shows higher maximum load capacity compared with HSC structural reinforced concrete beam. The first crack load capacity increase ranging from 11,284% up to 16,03%. Based on the experimental test results, it can be suggested to apply partial depth of HSC and HFRC; 50% HSC and 50% HFRC on static determinate RC beam.Keywords: Composite Reinforced Concrete Beam, HFRC, HSC, Full Scale Flexural Test